Aplikasi Kompos Gulma Siam Chromolaena odorata terhadap Sifat Kimia Tanah dan Performa Tanaman Cabai - Vira Kusuma Dewi; Nugoho Susetyo Putra; Benito Purwanto; Sri Hartati; Santika Sari (Fakultas Pertanian Universitas Padjadjaran, 2018)
Chromolaena odorata (L.) is a potential compost since it has high biomass and contains calcium, manganese, potassium and nitrogen. The aim of this research was to know the potency of siam weed Chromolaena odorata compost on soil chemical and chili plant performance. The experiment was arranged in factorial randomized block design consisted of two factors and three replications. The first factor was variety of fertilizer (no fertilizer, cow manure, siam weed compost and inorganic fertilizers) and the second one was the tanglefoot (with and without tanglefoot). Overall, the results of study showed that C. odorata compost could increased crop performance when compared with the other fertilizers in terms of number of fruits, fresh/dry weight of fruits, dry weight of crops, and N-total (leaf, stem, root and fruit), though there was no difference in fresh weight of crops among treatments. Furthermore, the effect of siam weed compost was not significantly different on soil chemical if compared with all treatments. This study is likely suggesting that C. odorata compost gives a positive effect to crops performance and soil chemicals.Keywords: Chili, Chromolaena odorata, compost fertilizer, tanglefoot